Catalyzing Quality Improvement in the HIV Control Programme of Rivers State: Evidence of the Impact of Clinical Mentorship Programme - , Golden Chukwuemeka Owhonda; , Patrick Sunday Dakum; , Charles Mensah; , Olayemi Kinmilola Olupitan; , Rogers Bariture Kanee; , Eric Osamudiamwen Aigbogun Jr; , Ufuoma Edewor (Archives of Current Research International, 2022)
Background: Rivers State had a huge burden of PLHIV, and the UNAIDS Spectrum 2019 model projected the total number of PLHIV in the State in 2020 to be 184,551. The semblance of HIV treatment care and support program, commencing after the diagnosis of the first reported case of HIV, dates as far back as 1989 when HIV was first diagnosed in the State. However, thirty years later, the treatment coverage had remained poor, despite the support of development partners. So, there was a strong need to strengthen the capacity of all critical actors in the program to achieve the objectives around the three-95s of the End AIDS Strategy, using strategic yet novel interventions such as the CMP. This research aims to determine how much of an effect a clinical mentorship program has had on enhancing Rivers State's HIV control efforts. Methodology: The clinical mentorship framework was implemented and amortized to strengthen all layers of ongoing interventions to catalyze better quality improvement. Clinical Mentors were recruited as indigenous medical experts knowledgeable in HIV service delivery and trained on quality improvement strategies and the use of virtual audiovisual systems, data management, team command system, and problem-solving models for the timeous impact of achieving key programme targets. Results: The Clinical Mentorship Programme (CMP) supported the achievement of a 690% & 23% increase in TX_CURR & PVLS, respectively, 27 months after its introduction. The TX_CURR improved by a factor of 7.9, and the PVLS increased by a factor of 1.23. The TX_CURR and PVLS achieved >100% of the target. The CMP was a success in the Rivers State HIV Control Programme. Conclusion: Though other ongoing cross-cutting interventions may mask any reported advances in key performance indicators, the introduction of the CMP appears to have corresponded with and largely (but not entirely) stimulated the observed achievements and impact on the monitored key program metrics. It is recommended for similar contexts and public health programs in places with limited resources and significant unmet needs.